Here for Everyone - Osterhues, Denise (2020)
Denise Osterhues SPECIAL EVENT Virtual Event - Food Loss and Waste – Can we end it by 2030 while dealing with the COVID-19 pandemic? Co-Organized by IFPRI, Champions 12.3, Embassy of Denmark in Washington, DC, World Resources Institute (WRI) MAY 12, 2020 - 09:00 AM TO 10:15 AM EDT